Can regular physical exercise be a treatment for panic disorder? A systematic review - Machado, Sergio (2022)
Introduction: In the last few decades, exercise has been explored as a potential tool to reduce symptoms experienced by patients with panic disorder (PD). This systematic review aims to assess the effects of regular exercise interventions on panic severity, global anxiety, and depression symptoms of these patients. Areas covered: A search was conducted on PubMed, ISI Web of Science, and Cochrane Central Register of Controlled Trials using search terms related to PD and exercise. Eight trials were included, Furthermore, regular exercise programs presented different methodological characteristics. There is o clear evidence indicating that regular exercise programs (at least two 20-minute sessions per week for at least 6 weeks) reduce panic-related symptoms. Regular exercise is effective in improving global anxiety measures and depression. Expert opinion: Continuous aerobic exercise is the main type of intervention in the literature, generally providing a limited prescription. Currently, it is recommended the interval training, with intense and shorter stimuli, and long-term duration trials. However, despite the use of self-selected intensities and control based on the internal load be interesting as recommendation to increase adherence, careful is needed regarding training prescription due to scarce evidence.